Problematika Pembelajaran Nahwu Bagi Mahasiswa Sekolah Tinggi Agama Islam Hidayatuttullab Kediri - Moh Aziz Arifin (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2022)
the research objectives in this research, they are as follows: 1) description students' difficulties as grammar in the Islamic University Hidayatut Thullab Kediri. 2) description the factors of students' difficulties as grammar The Islamic University Hidayatut Thullab Kediri. The types of research, it is used by qualitative research, it is field research that uses the phenomenological and descriptive exploratory approach. Qualitative methods from research that produce data in the form of written or spoken words from people and behaviors that enable them to be observed. The research result is 1) Students' difficulties in studying grammar at The Islamic University Hidayatut Thullab Kediri, they are: students ’difficulty with grammar concepts, students’ difficulty in synthesizing grammar, students ’difficulty in training useful sentence synthesis. 2) Factors of students' difficulties in studying grammar at The Islamic University Hidayatut Thullab Kediri, it is divided into two parts: a) The internal factor is the factor of students themselves who still lack the motivation for continuous learning of grammar and the students ’desire to study grammar. b) The external factor affects the curriculum, the book, and the teacher.